Linguistic Habituation as a Hidden Curriculum in Islamic Moral Education: Polite Speech and the Formation of Adab - Annabil, Zidan; Ningsih, Tutuk; Yahya, Slamet; Hammam, Muhammad (Journal of Islamic Education Research, 2026)
This study examines the cultivation of Islamic moral education through linguistic habituation grounded in local wisdom, and positions polite speech as a hidden curriculum for the formation of adab within the pesantren environment. It specifically explores the pedagogical role of everyday linguistics practices in shaping students’ moral dispositions beyond formal religious instruction. A qualitative case study was conducted in an Islamic boarding school, involving 18 purposively selected informants, including a kyai, three ustadz, two administrators, and twelve santri. Data were collected through prolonged participant observation, in-depth semi-structured interviews, and analysis of institutional documents. Trustworthiness was ensured through source and method triangulation, member checking and iterative thematic analysis guided by an interactive analytical model. The findings indicate that polite language, particularly the habitual use of Javanese Krama Inggil, functions not as explicit linguistic instruction but as a culturally embedded moral practice integrated into daily life. Such linguistic habituation fosters verbal politeness, emotional self-control, humility (tawadhu’), and respect toward teachers and peers, thereby cultivating an orderly, low-conflict, and socially harmonious communicative climate. Language thus operates as a mechanism of moral self-regulation functioning as an implicit moral infrastructure that shapes students’ character through continuous interaction. The novelty of this study lies in reconceptualizing language as a core pedagogical instrument and hidden curriculum within Islamic moral education, rather than merely as a communicative or cultural medium. This study contributes theoretically by integrating Islamic moral pedagogy, virtue ethics, and hidden curriculum theory, while practically proposing a context-sensitive model of adab formation adaptable to diverse Islamic educational settings.